Effects of zero burning waste on the quality of liquid fertilizer and vermicompost - Jaya, Adi; Lautt, Bambang S.; Antang, Emmy U.; Sibot, Sosilawaty; Dohong, Salampak; Surawijaya, Panji; Dohong, Salundik (International Journal of Agricultural and Biological Engineering, 2020)
Peatland is an important ecosystem in Indonesia. But in almost every dry season, drained peatlands have been subject to detrimental wildfires. As a response, the government has explicitly prohibited the burning of land since 2016. To clear the land of crop residues and conduct zero burning practices, one alternative method is to utilize the waste biomass to support the cultivation of earthworms (vermiculture). This study examined the quality of liquid fertilizers and compost produced from vermiculture using a completely randomized factorial design, consisting of two treatment factors. The first factor was worm type, with two species used in this research named Lumbricus rubellus and Eudrilus eugeniae. The second factor was the type of feed provided to the worms, comprising no feed (control), vegetable waste, and crop residue waste resulting from zero burning land preparation. The type of feed significantly affected the pH value of the liquid fertilizer produced by the vermiculture but did not significantly affect the nutrient contents (N, P, and K). The combination of the types of earthworms and types of feed significantly affected the pH value of the vermicompost. The combination of worm types and feed types had a significant effect on exchangeable Ca, but not on exchangeable Mg, Na, and K. In combination, green vegetable waste and Lumbricus rubellus produced the greatest effect on soil CEC. However, for Base Saturation, the control (no food) and Eudrilus eugeniae showed the highest value. Types of worms and types of feed had a significant effect on the exchangeable Mg, while the other three parameters made no significant differences. Zero burning waste and Eudrilus eugeniae provide a better exchangeable Ca and Mg. In contrast, no-feeding and Eudrilus eugeniae have a better effect on exchangeable Na and K. Types of worms and types of feed did not significantly affect the weight of worm colonies, but the addition of feed increased the weight of worms with the highest weight resulting from the use of zero burning waste feed. The results showed that crop residue wastes were potentially good as a feed for earthworms. Keywords: liquid organic fertilizer, vermicompost, Lumbricus rubellus, Eudrilus eugeniae, zero burning waste, crop residue, land preparation DOI: 10.25165/j.ijabe.20201304.4814 Citation: Jaya A, Lautt B S, Antang E U, Sibot S, Dohong S, Surawijaya P, et al. Effects of zero burning waste on the quality of liquid fertilizer and vermicompost. Int J Agric & Biol Eng, 2020; 13(4): 159–165.